Perspectives on Implementing Micro-credentials in the Commonwealth Caribbean: A Survey of Stakeholders - McGreal, Rory (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2025)
Micro-credentials (MCs) have emerged as a transformative tool in education and workforce development, offering flexible, targeted learning opportunities that align with the principles of lifelong learning. This paper presents the findings of a survey conducted among stakeholders in the Commonwealth Caribbean in a baseline study to gauge their awareness, experiences, and attitudes toward MCs. The study reveals that while a majority of respondents are familiar with MCs, significant barriers such as lack of awareness, resistance to change, and limited access to technology hinder their widespread adoption. The paper highlights the potential of MCs to address regional flexible learning and skills gaps, support workforce development, and promote social inclusion, while also emphasizing the need for clear policies, quality assurance frameworks, and stakeholder collaboration. By applying the Lifelong Learning Paradigm, the paper provides a comprehensive framework for understanding the role of MCs in supporting continuous learning, skill development and adaptability. The findings underscore the importance of aligning MCs with industry needs, leveraging technology, and fostering a supportive ecosystem to ensure their successful implementation in the Caribbean. The paper concludes with actionable recommendations for policymakers, educators, and employers to integrate MCs into the region’s lifelong learning landscape.